Fission yields and cross section uncertainty propagation in Boltzmann/Bateman coupled problems: Global and local parameters analysis with a focus on MTR. (December 2016) - Frosio, Thomas; Bonaccorsi, Thomas; Blaise, Patrick
Highlights: Nuclear data uncertainty propagation for neutronic quantities in coupled problems. Uncertainties are detailed for local isotopic concentrations and local power maps. Correlations are built between space areas of the core and for different burnups. Abstract: In a previous paper, a method was investigated to calculate sensitivity coefficients in coupled Boltzmann/Bateman problem for nuclear data (ND) uncertainties propagation on the reactivity. Different methodologies were discussed and applied on an actual example of multigroup cross section uncertainty problem for a 2D Material Testing Reactor (MTR) benchmark. It was shown that differences between methods arose from correlations between input parameters, as far as the method enables to take them into account. Those methods, unlike Monte Carlo (MC) sampling for uncertainty propagation and quantification (UQ), allow obtaining sensitivity coefficients, as well as correlations values between nuclear data, during the depletion calculation for the parameters of interest. This work is here extended to local parameters such as power factors and isotopic concentrations. It also includes fission yield (FY) uncertainty propagation, on both reactivity and power factors. Furthermore, it introduces a new methodology enabling to decorrelate direct and transmutation terms for local quantities: a Monte-Carlo method using built samples from a multidimensional Gaussian law is used to extend the previous studies, and propagate fission yield uncertainties from the CEA's COMAC covariance file. It is shown that, for power factors, the most impacting ND are the scattering reactions, principally coming from 27 Al and (bounded hydrogen in) H2 O. The overall effect is a reduction of the propagated uncertainties throughout the cycle thanks to negatively correlated terms. For fission yield (FY), the results show that neither reactivity nor local power factors are strongly affected by uncertainties. However, they have a non-negligible impact on some isotopic concentrations, and can lead to biases on some burnup indicators.